Germination of Pomegrate Seeds (Punica granatum L.) on Concentration Treatment and Soaking Time in Sulfuric Acid (H2SO4) - Lubis, Hafni Wahyuni; Faisal, Faisal; Nazimah, Nazimah; Ismadi, Ismadi; Handayani, Rd Selvy (Journal of Tropical Horticulture, 2022)
One of the medicinal plants that contain high antioxidants and have an important role in nutritional needs is pomegranate. Pomegranate plant propagation can be done generative and vegetatively.  Sexual propagation is constrained because pomegranate plants have dormancy properties and hard seed coats that cause seed germination to take a long time. Effectiveness of sulfuric acid is used to break dormancy in hard seed coats so that the inhibition process goes well, and the germination process is faster.  This research aims to determine the effect of concentration and duration of immersion in sulfuric acid solution on the germination of pomegranate seeds. This research used a two-factor randomized block design. The first factor was sulfuric acid concentration (control, 65%, 70%, 75%).  The second factor is the immersion time (without immersion, 5 minutes. 10 minutes. 15 minutes).  Each treatment was repeated 3 times.